Economic development and income distribution in Argentina - United Nations (New York : United Nations, 1969)
This book examines the relationship between economic development and income distribution in Argentina. Chapter one provides a brief historical sketch of some features of the development of the Argentine economy; chapter two provides an analysis of the income distribution structure in 1961; chapter three contains and analysis of the changes in the overall distribution and the structure of the distribution by socio-economic group; chapter four extends the analysis to other major aspects which limits the applicability of the estimates to a welfare analysis; chapter five is a broader analysis of the changes in income distribution; and chapter six analyses the role of public policy in the changes in the distribution of income and its structure.
"United Nations publication. Sales no.: E.68.II.G.6."
Includes bibliographical references.
lje 12/12/18
Loans
Keywords: Income distribution; Argentina